2013
DOI: 10.1080/09581596.2013.796340
|View full text |Cite
|
Sign up to set email alerts
|

Tracking governance: advice to mothers about managing the behaviour of their children in a leading Canadian women’s magazine during two disease regimes

Abstract: This paper explores how advice to mothers about raising healthy children differs in two distinct disease regimes as portrayed in articles in the preeminent Canadian women's magazine Chatelaine about 50 years apart, 1928-1944 and 1990-2012. The paper compares intensive mothering, medicalization and the perception of risk. It suggests that both intensive mothering and medicalization are continuous from time period to time period (although the content of both mothering and medicalization differ in the two period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…In mainstream (aimed primarily at White women) magazine, children's mental health issues are framed in terms of medicalisation, individualism and intensive mothering (Clarke, 2014). In the mainstream magazines, the focus is on directing the individual reader (mother) to be aware of risks to her child and to be diligent in her attention to her child's behavioural and emotional expression in order that the child grow up to be normal, good and successful.…”
Section: Discussionmentioning
confidence: 99%
“…In mainstream (aimed primarily at White women) magazine, children's mental health issues are framed in terms of medicalisation, individualism and intensive mothering (Clarke, 2014). In the mainstream magazines, the focus is on directing the individual reader (mother) to be aware of risks to her child and to be diligent in her attention to her child's behavioural and emotional expression in order that the child grow up to be normal, good and successful.…”
Section: Discussionmentioning
confidence: 99%
“…Latent analysis looks for the implicit, underlying meaning (Neuman, 2010). (Clarke, 2013(Clarke, , 2014. I have combined the answers to the first two questions in the ensuing analysis as they were mostly intertwined in the data.…”
Section: Discussionmentioning
confidence: 99%
“…Bullying also imbricates some aspects of two other contemporary theories that in different ways pathologise the individual: medicalisation or the growth in medical definitions of reality (especially as related to mental illness in the perpetrator and/or the victim) and criminalisation. The medicalisation, particularly psychiatrisation (Le Francois, ), of childhood is well documented (see, for example Clarke, , ). The rate of criminalisation of some children's behaviours (especially externalising, violent or aggressive behaviours) is also growing (Stout and Holleran, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This message, as mentioned above (but see Hardyment, 2007 andStearns, 2003 for details), has been partly underpinned by an increasingly prominent framing of the child as a fragile being whose development is continuously at risk of being disturbed or impaired. Juanne Clarke and colleagues have conducted several historical studies of magazines (Clarke, 2011(Clarke, , 2014Clarke et al, 2014) and have similarly found a strong emphasis on the need for parents to consult with medical and psychological experts and on the responsibility that parents, particularly the mother, have for managing childhood risks. This is not unique to the North American context, however.…”
Section: "Don't Worry": Figurations Of the Child In A Swedish Parentimentioning
confidence: 99%